Paternal Negative Parenting and Ill-Being in Adolescence: Examining the Moderating Role of Resilience - Lampropoulou, Aikaterini (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2024)
Objectives: This study explores the associations between paternal negative parenting—specifically rejection, control/overprotection, and anxious rearing—and adolescent ill-being. Additionally, it examines whether resilience moderates these relationships, potentially buffering the negative effects of paternal negative parenting on adolescent well-being.Methods: A cross-sectional study was conducted with 331 adolescents (ages 12-16) from junior and senior high schools in Attica, Greece. Participants completed the Berne Questionnaire of Subjective Well-Being/Youth Form (BSW/Y), the Egna Minnen Betraffande Uppfostran (EMBU-C) questionnaire, and the Resilience Scale. Correlation analyses, multiple regression models, and moderation analyses were employed to examine the associations between paternal negative parenting, resilience, and adolescent ill-being.Results: Results showed that paternal rejection, though the least reported, was the strongest predictor of adolescent ill-being. Resilience was negatively associated with paternal rejection and significantly predicted well-being outcomes. A moderation analysis revealed that resilience buffered the negative association between paternal control/overprotection and adolescent ill-being, with lower resilience amplifying the adverse effects. Younger adolescents perceived their fathers as more controlling and overprotective, while girls reported higher ill-being than boys.Implications: These findings highlight the pivotal role of resilience in mitigating the adverse effects of paternal negative parenting. Intervention efforts should prioritize the reduction of paternal rejection and control/overprotection, while simultaneously fostering resilience in adolescents. Integrating resilience-building components and encouraging positive paternal involvement may enhance psychosocial outcomes and promote adaptive developmental trajectories.